Analisis Sistem Bagi Hasil Produk Mudarabah pada Pembiayaan Modal Usaha Bank Syariah (Studi Kasus BPRS Bhakti Sumekar Kantor Cabang Pragaan) - Rahman, Holilur; Hasanah, Rif’atul (Multiverse: Open Multidisciplinary Journal, 2023)
Business capital financing is a financial product offered by banks to support the growth and expansion of customer businesses. Customers or financed parties are required to repay the funds or bills within a specified period, in exchange for profit sharing. This study focuses on the profit sharing system in business capital financing products at BPRS Bhakti Sumekar Pragaan branch office, particularly examining its compliance with Islamic business ethics. Using qualitative field research, the study employed interviews with the branch office's leadership and accounting officers as the primary data collection method. The findings revealed that while the branch office utilizes a profit and loss sharing system, it does not fully adhere to Shari'ah principles. The profit sharing amount remains constant each month, unrelated to actual business profits, as it relies on assumptions and profit projections. This approach stems from the bank's concerns regarding customers' honesty in reporting their business profits. To mitigate the risk of non-payment, the bank ensures fixed principal installments and consistent profit sharing amounts throughout the financing period